Total factor carbon emission productivity in China’s manufacturing industry: a study considering indirect carbon emissions - Hao, Zhijie; Wang, Xiaotian (Frontiers in Environmental Science, 2025)
Considering the backdrop of indirect carbon emissions, this paper aims to examine the patterns and influencing factors of total factor carbon emission productivity (TFCEP) in China’s manufacturing sub-sectors and propose policy recommendations for improving carbon emission performance. Based on empirical data from China’s manufacturing industry from 2005 to 2020 (covering the 11th Five-Year Plan (FYP) to the 13th FYP), this paper combines direct and indirect carbon emissions to present a more comprehensive formula for calculating sectoral CO2 emissions. The global Malmquist–Luenberger (GML) productivity index is used to calculate TFCEP, followed by an analysis of the influencing factors using a mixed regression model. Despite an average annual increase of 3.4% in the TFCEP of the overall manufacturing sector, contributing 34.7% to output growth, comparative analysis indicates a decline in the sector’s overall TFCEP across the three FYPs. The TFCEP decomposition index of the manufacturing sub-sectors shows industry heterogeneity. Empirical analyses have proven that technological innovation and environmental regulatory policies are the most effective means to enhance TFCEP and may serve as the primary leverage to achieve the “dual carbon” goals. The level of electrification is innovatively introduced to characterize the energy structure, and its relationship with TFCEP exhibits an inverted U-shaped curve. This finding suggests that electrification policies should be tailored to the specific electrification stage of each industry.